Chromium toxicity and tolerance mechanisms in plants through cross-talk of secondary messengers: An overview of pathways and mechanisms. (1st March 2023) - Sharma, Pooja; Singh, Surendra Pratap; Tripathi, Rudra Deo; Tong, Yen Wah
Abstract: Environmental sources of chromium (Cr) such as solid waste, battery chemicals, industrial /waste, automotive exhaust emissions, mineral mining, fertilizers, and pesticides, have detrimental effects on plants. An excessive amount of Cr exposure can lead to toxic accumulations in human, animal, and plant tissues. In plants, diverse signaling molecules like hydrogen sulfide (H2 S) and nitric oxide (NO) play multiple roles during Cr stress. Consequently, the molecular mechanisms of Cr toxicity in plants, such as metal binding, modifying enzyme activity, and damaging cells are examined by several studies. The reactive oxygen species (ROS) that are formed when Cr reacts with lipids, membranes, DNA, proteins, and carbohydrates are all responsible for damage caused by Cr. ROS regulate plant growth, programmed cell death (PCD), cell cycle, pathogen defense, systemic communication, abiotic stress responses, and growth. Plants accumulate Cr mostly through the root system, with very little movement to the shoots. The characterization of stress-inducible proteins and metabolites involved in Cr tolerance and cross-talk messengers has been made possible due to recent advances in metabolomics, transcriptomics, and proteomics. This review discusses Cr absorption, translocation, subcellular distribution, and cross-talk between secondary messengers as mechanisms responsible for Cr toxicity and tolerance in plants. To mitigate this problem, soil-plant systems need to be monitored for the biogeochemical behavior of Cr and the identification of secondary messengers in plants.